Kinerja Pengawas Dalam Meningkatkan Profesionalisme Guru di SMA Negeri 1 Pacet - Muhammad Hasyim Mubarok; M. Asy’ari; Andri Andri (CV. Pusdikra Mitra Jaya, 2023)
The focus of this research is on the performance of supervisors in improving the professionalism of teachers at SMA Negeri 1 Pacet and the results of their performance in enhancing the professionalism of teachers at SMA Negeri 1 Pacet. This study adopts a qualitative approach with a descriptive design, and the location of the research is at SMA Negeri 1 Pacet. The data collection methods include interviews, observation, and documentation. Data analysis is conducted using the Mathew Miles and A. Michael Huberman model, which involves data reduction, data display, and conclusion drawing (verification). The results indicate that the performance of supervisors at SMA Negeri 1 Pacet has not met the expected standards, as they have not been able to carry out their duties to the fullest. This includes monitoring the content and process standards, handling counseling problems, and providing professional training for teachers and the school principal. The professionalism of teachers at SMA Negeri 1 Pacet is also lacking or has not met expectations. Indicators of this lack of professionalism include inadequate skills in lesson planning and management. Furthermore, the performance of supervisors in enhancing the professionalism of teachers at SMA Negeri 1 Pacet has not been effective. The indicators include the lack of impact of supervisors' performance on enhancing teachers' skills in lesson planning, implementation, and assessment. The factors hindering the performance of supervisors include their lack of professionalism and some teachers' reluctance to follow the guidance provided by supervisors. The solution to these issues is to enhance the professionalism of supervisors and improve communication with the teachers they supervise.